Rethinking teacher action research as Bildung: a phenomenological approach to professional development - Kim, Jeong-Hee (My University, 2013)
In this article, I engage in exploring how teacher action research can be theorized as professional development that contributes to the teacher’s ongoing, ontological growth as a being and a professional. I approach teacher action research from an interpretive phenomenological perspective to understand the meaning of teachers’ lived experiences of conducting action research. The purpose of this research is to rethink teacher action research as Bildung, a phenomenological approach to professional development that explores the process of the teacher’s growth that is constantly evolving and becoming. By focusing on five teachers’ lived experiences of conducting action research in their classrooms, I delve into how teacher action research contributes to the teacher’s Bildung, the human way of cultivating process of the self as a teacher.
Teacher action research as Bildung: An application of Gadamer’s philosophical hermeneutics to teacher professional development
Keywords: Teacher action research; Philosophical hermeneutics; Bildung; Professional development; Phenomenology